AN APPROACH FOR DERIVATION OF MARKOV-TYPE INEQUALITIES IN $L_2$ NORMS - Aleksov, Dragomir (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2013)
An approach for derivation of Markov-type inequalities in $L_2$ norms proposed in [9] is applied to the classical case of a constant weight function. According to a result of E. Schmidt, the sharp constant in this inequality is asymptotically equal to \( \frac{n^2}{π} \). We obtain upper and lower bounds for the best constant.